Biochemical characterization of cytidine triphosphate synthase (CTPase) from Toxoplasma gondii (2015)
Toxoplasma gondii is a ubiquitous intracellular parasite with worldwide distribution. New antiparasitic drugs with greater effectiveness in controlling T. gondii are necessary. The enzymes of de novo pyrimidine biosynthetic pathway are considered potential drug targets, because they are required for the parasite' s virulence and survival. Cytidine triphosphate synthase (CTPase) catalyzes the conversion of UTP to CTP, the final step in the production of cytidine nucleotides, and the first step in the formation of phospholipid intermediates. In many organisms, CTPase also plays a structural role in vivo, forming filaments together with other proteins. The function of these filaments is unknown, and identification of their protein components could aid in elucidating function. Our goal was the biochemical characterization of cytidine triphosphate synthase of T. gondii (TgCTPase), and generated tools to study protein-protein interactions, in order to begin to determine its importance as a potential antiparasitic target